SERVICE AND NETWORK MODELING FOR IMPLEMENTATION OF POWERLINE REMOTE MONITORING OF ELECTRICAL POWER METERING IN TANZANIA - Anatory, J.; Mvungi, N. H.; Kissaka, M. M. (Tanzania Journal of Engineering and Technology, 2018)
Abstract